Influence of Acetylated Annealed Starch on the Release of β-Escin from the Anionic and Non-Ionic Hydrophilic Gels - Justyna Kobryń; Tomasz Zięba; Sandra Karolina Sowa; Witold Musiał (MDPI AG, 2020)
Naturally sourced products introduced to human nutrition and rediscovered for therapy include polysaccharides from potatoes. The starch may obtain unique properties via acetylation with acetic anhydride at 13 cm3/100 g of starch as the basic dose of reagent used in industrial conditions. The hydrogel formulation was applied as a carrier for escin included in the dry extract of Aesculus hippocastanum. Six hydrogels were evaluated (methylcellulose, polyacrylic acid-Carbopol 980 NF and polyacrylate crosspolymer 11—Aristoflex Velvet) with various concentrations of the modified starch. The kinetic studies of in vitro β-escin release were carried out in purified water at 37 ± 0.5 °C using a paddle apparatus at 50 rpm and a time period of 7 h. The criterion for the most suitable model was based on a high correlation coefficient of evaluated release profiles. The addition of modified annealed acetylated potato starch resulted in prolongation of β-escin release.